2013
DOI: 10.1002/hep.26306
|View full text |Cite
|
Sign up to set email alerts
|

Good long-term outcome of Budd-Chiari syndrome with a step-wise management

Abstract: Budd-Chiari syndrome (BCS) is a rare, life-threatening disease caused by obstruction of hepatic venous outflow. The aim of the study was to assess long-term outcome and identify prognostic factors in BCS patients managed by a step-wise approach using anticoagulation, angioplasty/thrombolysis, transjugular intrahepatic portosystemic shunting (TIPS), and orthotopic liver transplantation (OLT). We reviewed long-term data on 157 patients previously included by the European Network for Vascular Disorders of the Liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
241
4
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(285 citation statements)
references
References 71 publications
15
241
4
5
Order By: Relevance
“…Moreover, patients receiving only medical therapy often have a bad outcome. In fact, the widest longterm multicenter experience on BCS reported that almost 30% of patients who received only medical therapy died, a high rate considering the availability of further effective invasive treatments [8] . Furthermore, a recent systematic review confirmed the bad outcome of BCS on only medical therapy, with survival worsening during long-term follow up in patients on only medical therapy [46] .…”
Section: Early Versus Delayed Interventional Treatment Of Bcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, patients receiving only medical therapy often have a bad outcome. In fact, the widest longterm multicenter experience on BCS reported that almost 30% of patients who received only medical therapy died, a high rate considering the availability of further effective invasive treatments [8] . Furthermore, a recent systematic review confirmed the bad outcome of BCS on only medical therapy, with survival worsening during long-term follow up in patients on only medical therapy [46] .…”
Section: Early Versus Delayed Interventional Treatment Of Bcsmentioning
confidence: 99%
“…In fact, hepatocellular carcinoma (HCC) development is surely a concern during follow up of BCS [6] . Moreover, the outcome of underlying disease is other issue, since about 10% of the patients are reported to die because of hematological disease progression [7,8] . Finally, both different sources of bleeding [9] and thrombosis of other organs [8] are further complications potentially affecting BCS outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 As stated before, medical therapy is suggested as the first-line treatment, angioplasty/stenting the second-line, transjugular intrahepatic portosystemic shunt (TIPS) the further step, and liver transplantation (LT) the last chance. 2 Step-wise management suggests moving forward when no response to therapy appears.…”
Section: Budd-chiari Syndrome Management: Timing Of Treatment Is An Omentioning
confidence: 99%
“…Overall survival was 74% at 5 years. 1 TIPS is the most used treatment for BCS 2,3 because it is effective also in the case of thrombosis extension to the portal vein tree. [5][6][7] However, timing for TIPS was not stated.…”
Section: Budd-chiari Syndrome Management: Timing Of Treatment Is An Omentioning
confidence: 99%